2019
DOI: 10.1007/s00268-019-05316-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial on Autologous Platelet‐Rich Plasma Versus Saline Dressing in Treatment of Non‐healing Diabetic Foot Ulcers

Abstract: Background This randomized clinical trial was conducted to assess the role of platelet-rich plasma (PRP) gel as a treatment of clean non-healing diabetic foot ulcer (DFU) in comparison with regular dressing with saline as a control. Methods Patients with DFU were randomly assigned to one of two equal groups: group I received dressing with PRP gel and group II received regular saline dressing. The main outcomes of the study were percent reduction in the dimensions of the DFU, healing of DFU, and complications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 26 publications
3
106
1
Order By: Relevance
“…Refractory pressure injuries are mainly characterized by persistent symptoms and severe wound infections; these characteristics are related to blocked microcirculation, reduced local blood flow, attenuated phagocytosis, accelerated destruction of tissue proteins, and wound infection. Therefore, improving cell migration in scaffolds, activating cell proliferative activity, and reducing wound inflammatory responses are key parameters involved in the acceleration of wound repair (10,11). NPWT is a common method to treat refractory pressure injuries and has the following advantages: it insulates the wound and avoids secondary infection; promotes the exudation of wounded and necrotic tissue from the body, and increases blood flow in the wound and accelerates the growth of granulation tissue through negative pressure stimulation.…”
Section: ' Discussionmentioning
confidence: 99%
“…Refractory pressure injuries are mainly characterized by persistent symptoms and severe wound infections; these characteristics are related to blocked microcirculation, reduced local blood flow, attenuated phagocytosis, accelerated destruction of tissue proteins, and wound infection. Therefore, improving cell migration in scaffolds, activating cell proliferative activity, and reducing wound inflammatory responses are key parameters involved in the acceleration of wound repair (10,11). NPWT is a common method to treat refractory pressure injuries and has the following advantages: it insulates the wound and avoids secondary infection; promotes the exudation of wounded and necrotic tissue from the body, and increases blood flow in the wound and accelerates the growth of granulation tissue through negative pressure stimulation.…”
Section: ' Discussionmentioning
confidence: 99%
“…In addition, PRP is used in the clinical treatment of acute and chronic wounds in an unconventional manner with good results. PRP can increase the healing rate of diabetic wounds, reduce the injury area of pressure ulcers and improve joint function in osteoarthritis (OA) [ 10–12 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the above studies were summarized in Table 4. [78][79][80][81][82][83][84][85] Furthermore, there are more studies to evaluate the efficacy and safety of PG for patients with diabetic ulcers, one study with 15 RCTs with 829 patients, 77 another study with 8 RCTs involved 431 participants. 86 These evidences suggested that PG was effective and safe, and feasible for diabetic ulcers.…”
Section: Human Clinical Studiesmentioning
confidence: 99%
“…Both studies suggested that the application of PG was an efficient and safe treatment option, for the treatment of oral cGvHD patients who do not respond to standard local treatment.PRP is a simple, low-cost, safe, minimally invasive, and effective technique in clinical trials on DFU, researches include randomized controlled trial (RCT), meta-analysis, and system review. Elsaid et al78 conducted an RCT with 24 patients to assess PG as a treatment of clean non-healing DFU in comparison with regular dressing with saline as a control. Results showed that compared to regular saline dressing, PG as a dressing for chronic DFU resulted in a more significant reduction in the size of the ulcer and the time to reach the point of maximal possible healing was shorter.…”
mentioning
confidence: 99%